Comparative Study of Factors Affecting Employees in Private and Public Digital TV Companies - Dejbandit, Chalothorn; Sangroengrob, Tibrat (Siam University Journal of Business Administration, 2021)
This research aims to study the effects of job characteristics, policies, colleagues, incentives, leadership, and communication on the employees in two digital TV channel companies, namely, G Company (private company) and N Company (public company). The research was conducted by analyzing the responses from the total number of 400 participants (200 participants from each company). The researcher uses the questionnaire as an instrument for collecting the data. Additionally, the target group is from convenience sampling as well as the data is analyzed with descriptive statistics and inferential statistics by using the exploratory factor analysis: EFA to analyze the factors which are independent variables and using the binary logistic regression to test the research hypothesis. The result found that the exploratory factors, which are the independent variables, can classify the group of factors affecting the employees in the TV digital channels of G and N companies into 7 factors including job-interest, job-autonomy, policy, colleague, incentive, leadership, and communication. For the binary logistic regression, it is found that 5 factors influencing the employees between G Company and N Company are different with the statistical significance at the 0.05 level (the G Company is determined to be 0 and N Company is determined to be 1). To state the 5 factors, the first factor, job-interest, contains 0.628 as a B value, the second factor, job-autonomy, contains -0.480 as a B value, the third factor, policy, contains -1.575 as a B value, the fourth factor, incentive, contains -1.764 as a B value, and the last factor, leadership, contains -1.029 as a B value. Furthermore, the factors of colleague and communication which affect G Company and N Company are not different.